2018
DOI: 10.3847/1538-4357/aae36a
|View full text |Cite|
|
Sign up to set email alerts
|

Evolved Climates and Observational Discriminants for the TRAPPIST-1 Planetary System

Abstract: The TRAPPIST-1 planetary system provides an unprecedented opportunity to study terrestrial exoplanet evolution with the James Webb Space Telescope (JWST) and ground-based observatories. Since M dwarf planets likely experience extreme volatile loss, the TRAPPIST-1 planets may have highly evolved, possibly uninhabitable atmospheres. We used a versatile, 1D terrestrial planet climate model with line-by-line radiative transfer and mixing length convection (VPL Climate) coupled to a terrestrial photochemistry model… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
390
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 169 publications
(400 citation statements)
references
References 212 publications
8
390
1
1
Order By: Relevance
“…Its photochemical module is based on a photochemical code originally developed by Kasting et al (1979) and significantly updated and modernized as described in Zahnle et al (2006). The photochemical module has recently been updated as described in Lincowski et al (2018) with an expanded and higher resolution wavelength grid; and updated cross sections, quantum yields, and reaction rates. Tests comparing the upgraded model used here to the previous version suggest that the previous version may overestimate CH 4 abundances for the types of atmospheres that we simulate here by up to 50%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its photochemical module is based on a photochemical code originally developed by Kasting et al (1979) and significantly updated and modernized as described in Zahnle et al (2006). The photochemical module has recently been updated as described in Lincowski et al (2018) with an expanded and higher resolution wavelength grid; and updated cross sections, quantum yields, and reaction rates. Tests comparing the upgraded model used here to the previous version suggest that the previous version may overestimate CH 4 abundances for the types of atmospheres that we simulate here by up to 50%.…”
Section: Methodsmentioning
confidence: 99%
“…Tests comparing the upgraded model used here to the previous version suggest that the previous version may overestimate CH 4 abundances for the types of atmospheres that we simulate here by up to 50%. This upgraded model has been validated on Earth and Venus as described in Lincowski et al (2018). The climate module of Atmos was originally developed by Kasting & Ackerman (1986), and like the photochemical model has evolved considerably since this first incarnation.…”
Section: Methodsmentioning
confidence: 99%
“…-Habitable case 1 (Hab1): In this case, constituted of a modern Earth-like atmosphere of 1 bar of N 2 and 400 ppm of CO 2 , the dynamical core, the clouds and atmospheric processes are tested together. It is also the most widespread benchmark for habitable planets in the literature (Barstow and Irwin, 2016;Morley et al, 2017;Lincowski et al, 2018).…”
Section: Atmospheric Configurationsmentioning
confidence: 99%
“…Recent climate modeling has begun to explore how clouds affect the detection of transmission spectral features with JWST. Using the one-dimensional climate and photochemical models of Lincowski et al (2018), Lustig-Yaeger et al (2019) found that clouds inhibit the detection of water features on TRAPPIST-1e. However, three-dimensional simulations are necessary to accurately simulate cloud and water vapor mixing ratios.…”
Section: Introductionmentioning
confidence: 99%